PERENCANAAN GEOMETRIK DAN PERKERASAN LENTUR (Study Kasus: Jalur Jalan Lintas Selatan Sta.75+200 – Sta.83+510 Desa Mulyorejo Kecamatan Silo Kabupaten Jember) - Maulana, Galih Alif; ., Irawati .; Hamduwibawa, Rofi Budi (HEXAGON, 2017)
The plan for the construction of the Jalan Lintas Selatan (JLS) of Jember is the access of the southern road of Jember along 83,510 kilometers. JLS crossed 7 districts, which were Kencong, Gumukmas, Puger, Wuluhan, Ambulu, Tempurejo and Silo. As for Silo through Mulyorejo along 17.910 kilometers. Field conditions in JLS Mulyorejo are Perhutani land and farm village. The purpose and objectives of the Final Project (4 research sites) are to plan geometric and pavement thickness at JLS in Mulyorejo village with potential area with coffee and banana plants. In addition, Mulyorejo Village has a productive coffee management factory (PTPN.XII). From the research results (Horizontal arch): LC1 = 124.026 m, LC2 = 132.506 m, LC3 = 153.960 and LC4 = 220.868 m. For Vertical curvature: EV1 = -1.496 m, EV2 = -1.687, EV3 = + 0.6591 m and EV4 = -0.634 m.As for super elevation planning is + and - 2% transverse slope. In the thickness of pavement using the method of Bina Marga 2013 with CBR 7.5% (PU Bina Marga, 2016) with the following results: 4.00 cm thick AC WC, 13.5 thick AC BC, 15.00 thick LPA class A and 15.00 cm thick LPA class B.Keywords:Planning, Geometric and Pavement Thickness 2013.